Rose Mosaic Virus Disease: A Disease Caused by a Virus Complex and Symptoms on Roses and Management Practices - Susannah da Silva; Binoy Babu; Mathews L. Paret; Gary W. Knox; Fanny Iriarte; Barron Riddle; Matthew Orwat; Shawn T. Steed; E. Vanessa Campoverde; Svetlana Y. Folimonova (EDIS)
Rose mosaic virus disease is one of the most economically important diseases affecting roses, because a single symptomatic leaf can result in the rejection of complete shipments for wholesale or retail rose producers. It continues to be a problem in nursery production and landscapes. This 5-page document discusses the causes, symptoms, and management of this disease. Written by Susannah da Silva, Binoy Babu, Mathews L. Paret, Gary Knox, Fanny Iriarte, Barron Riddle, Matt Orwat, Shawn T. Steed, E. Vanessa Campoverde, and Svetlana Y. Folimonova and published by the UF/IFAS Plant Pathology Department, August 2018. http://edis.ifas.ufl.edu/pp338/